REGIONAL ECONOMIC PERFORMANCE AND PUBLIC SERVICE FACILITIES: AN ANALYSIS OF KLASSEN TYPOLOGY AND SCALOGRAM IN JAMBI PROVINCE - Putri Intan Suri; Rian Putra; Deki Irawan (Accounting Department, Politeknik Negeri Bandung, 2026)
Jambi Province consists of nine regencies and two cities with diverse topographical characteristics. Regional economic progress is generally determined by two primary indicators: economic growth and GRDP/capita. This study aims to analyze the development levels of regencies and cities in Jambi Province in relation to their public facilities. The research methodology employs the Klassen Typology to classify regional progress, Scalogram Analysis to determine public facility ownership, geographic and geo-economic mapping to identify the distribution of influence. The results identify four patterns of regional economic performance: one Developed Region, four Potential Regions, three Developing Regions, and three Lagging Regions. A notable finding indicates that the Developed Region is Muaro Jambi Regency, while Jambi City is positioned as a Lagging Region. More significantly, the ownership of public facilities doesn’t appear to dictate a region's progress. This suggests that regions prioritize functional access to public facilities over administrative ownership of the facilities themselves.